The novel compound heterozygous variants identified in a Chinese family with glucose phosphate isomerase deficiency and pathogenicity analysis - Yang Wang; Tao Liu; Jiaqi Liu; Yan Xiang; Lan Huang; Jiacheng Li; Xizhou An; Shengyan Cui; Zishuai Feng; Jie Yu (BMC, 2023)
Abstract Background and Aims: Glucose phosphate isomerase (GPI) deficiency is an extremely rare autosomal recessive disorder caused by mutations in the GPI gene. In this research, the proband displaying typical manifestations of haemolytic anaemia and his family members were recruited to analyse the pathogenicity of the detected variants. Methods: Peripheral blood samples were collected from the family members and genomic DNA was extracted and targeted for capture and sequencing. The effect of the candidate pathogenic variants on splicing was further investigated using the minigene splicing system. The computer simulation was also used for further analysis of the detected data. Results: The proband carried the compound heterozygous variants c.633 + 3 A > G and c.295G > T in the GPI gene, which have never been reported before. In the genealogy, co-segregation of the mutant genotype with the phenotype was established. The minigene study showed that intronic mutations resulted in abnormal pre-mRNA splicing. Specifically, the two aberrant transcripts: r.546_633del and r.633 + 1_633 + 2insGT were transcribed by the minigene plasmid expressing the c.633 + 3 A > G variant. The missense mutation c.295G > T in exon 3 resulted in altering glycine at codon 87 to cysteine which was predicted to be pathogenic in an in silico analysis. Deeper analyses revealed that the Gly87Cys missense mutation led to steric hindrance. Compared to the wild-type, the mutation G87C led to a significant increase in intermolecular forces. Conclusion: Overall, the novel compound heterozygous variants in the GPI gene contributed to the etiology of the disease. Genetic testing can assist in the diagnosis. The novel gene variants identified in the present study has further expanded the mutational spectrum of GPI deficiency, which can better guide family counselling.